Peran Orangtua Membimbing anak dalam belajar selama pandemi Covid-19 di Indonesia - Max Faisal Bahreizy (Yayasan Citra Dharma Cindekia, 2024)
The purpose of this research is to find out how the parents of Dinoyo Elementary School students are prepared to respond to online learning in the past 2020-2021. This research is a case study qualitative research that occurs during the online learning process. The collection technique used was interviews with several parents of students by remembering their role in their children's online learning process in 2020-2021 yesterday. The conclusion from this study is that there are three categories of parents in playing the role of guidance for their children. First, there are parents who do not fully understand technology which causes difficulties accompanying children in the online learning process. second, parents are technologically literate who can easily respond to online learning by guiding and supervising their children in online learning. third, parents play a role as motivation for their children in the learning process at home.